View of the Mandapa of the Suhaveshwar Temple - Temples of India Project Team (Jio Institute, 2024)
View of the mandapa (pillared hall) of the Suhaveshwar Temple as seen from its mukhamandapa (front porch). The mukhamandapa has two dwarf walls facing each other. The pillars of the mukhamandapa have cylindrical shafts in the upper half.